2014
DOI: 10.1371/journal.pone.0103365
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Functions of mRNA Metabolism Factors in Stress Defense and Aging of Caenorhabditis elegans

Abstract: Processing bodies (PBs) and stress granules (SGs) are related, cytoplasmic RNA-protein complexes that contribute to post-transcriptional gene regulation in all eukaryotic cells. Both structures contain translationally repressed mRNAs and several proteins involved in silencing, stabilization or degradation of mRNAs, especially under environmental stress. Here, we monitored the dynamic formation of PBs and SGs, in somatic cells of adult worms, using fluorescently tagged protein markers of each complex. Both comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(84 citation statements)
references
References 94 publications
(120 reference statements)
2
53
0
18
Order By: Relevance
“…Similarly, heat shock in C. elegans caused PAB-1 and TIAR-2 to form stress granules (Figures 2A and 2C; Figure S4A) (Murakami et al., 2012, Rousakis et al., 2014). When co-expressed, PAB-1 and TIAR-2 localized to the same stress granules (Figure S4B).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, heat shock in C. elegans caused PAB-1 and TIAR-2 to form stress granules (Figures 2A and 2C; Figure S4A) (Murakami et al., 2012, Rousakis et al., 2014). When co-expressed, PAB-1 and TIAR-2 localized to the same stress granules (Figure S4B).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that disruption of dcap-1 or dcap-2 genes, encoding the subunits of the mRNA decapping complex in worms, significantly shortens the extremely long life of class I daf-2(1368) mutants and reduces their resistance to stress [39]. Intriguingly though, the double mutant daf-2(e1368);dcap-1(tm3163) or daf-2(e1368);dcap-2(ok2023) animals were found to display increased levels of dauer arrest at the permissive temperature of 22°C compared with daf-2 single mutants (figure 1 a ).…”
Section: Resultsmentioning
confidence: 99%
“…This was also true for the class II daf-2(e1370) hypomorphic allele (figure 1 a ). The dcap-1(tm3163) phenotype proved to be less penetrant than the null dcap-2(ok2023) owing to an out-of-frame deletion that completely eliminates dcap-1 activity at 25°C, but retains a weak residual activity at lower temperatures [39]. At 22°C or 25°C, single decapping mutants did not form any dauers on their own, in the presence of food.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the co-localization experiments, CER157 animals expressing integrated copies of LSM-1::GFP were injected with a mix containing 80 ng/μL of a RFP::TIAR-1 construct (Rousakis et al 2014) and 20 ng/μL of the linearized roller marker pRF4 [rol-6(su1006)]. Transcriptional reporters, described in the Supplemental Material, were constructed by PCR fusion (Hobert 2002).…”
Section: Generation Of Transgenic Animalsmentioning
confidence: 99%